2020
DOI: 10.7554/elife.52712
|View full text |Cite
|
Sign up to set email alerts
|

Hair follicle stem cells regulate retinoid metabolism to maintain the self-renewal niche for melanocyte stem cells

Abstract: Metabolites are major biological parameters sensed by many cell types in vivo, whether they function as signaling mediators of SC and niche cross talk to regulate tissue regeneration is largely unknown. We show here that deletion of the Notch pathway co-factor RBP-J specifically in mouse HFSCs triggers adjacent McSCs to precociously differentiate in their shared niche. Transcriptome screen and in vivo functional studies revealed that the elevated level of retinoic acid (RA) caused by de-repression of RA metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…[167][168][169] Similarly, HFSCs deposit nephronectin on one side of the bulge, thus establishing a niche for the arrector pili muscle (APM), a muscle string that connects the epidermis with the hair follicle causing piloerection. 169,170 HFSCs also secrete Edn2, Wnt ligands and antagonists, KIT ligand, CXCL12, and Col17a1, 81,119,[171][172][173][174] which signal to the melanocyte SCs in the bulge to regulate coordinated responses during hair cycle.…”
Section: S I G Nalling From Hfsc S Towards the Surrounding S Kin Enmentioning
confidence: 99%
See 1 more Smart Citation
“…[167][168][169] Similarly, HFSCs deposit nephronectin on one side of the bulge, thus establishing a niche for the arrector pili muscle (APM), a muscle string that connects the epidermis with the hair follicle causing piloerection. 169,170 HFSCs also secrete Edn2, Wnt ligands and antagonists, KIT ligand, CXCL12, and Col17a1, 81,119,[171][172][173][174] which signal to the melanocyte SCs in the bulge to regulate coordinated responses during hair cycle.…”
Section: S I G Nalling From Hfsc S Towards the Surrounding S Kin Enmentioning
confidence: 99%
“…A recent study also sheds light on metabolites' role on niche regulation, as retinoic acid is found to be upstream of the melanocyte SC differentiation program. 174 Other components of the HFSC environment include the skin adipose tissue, whose progenitor cells signal to HFSCs for proper activation whereas the HF epithelium signals back for adipocyte production. 175 Last but not least are the mesenchymal cells, including the dermal papillae, which is essential in HFSC activation 18 and the dermal sheet, which was recently shown to function as a muscle important through each contractions for degradation of the epithelial hair bulb during catagen and for bringing the dermal papillae in close contact with the bulge.…”
Section: S I G Nalling From Hfsc S Towards the Surrounding S Kin Enmentioning
confidence: 99%
“…Two recent publications have shone light on the role cellular metabolites in McSC maintenance and, fascinatingly, how sympathetic innervation might impact on this cell population and lead to premature hair greying. [25,26] Taking the first of these, Lu et al [25] identified an important role for metabolic signaling between the epithelial and melanocyte SCs sharing in the HF bulge niche. Among the numerable signals received by SCs within the HF bulge at the onset of anagen, KIT-ligand is required by McSC to stimulate mobilization and differentiation.…”
Section: Intrafollicular Metabolism and External Stress Modulate Hairmentioning
confidence: 99%
“…Two recent publications have shone light on the role cellular metabolites in McSC maintenance and, fascinatingly, how sympathetic innervation might impact on this cell population and lead to premature hair greying. [ 25,26 ]…”
Section: Intrafollicular Metabolism and External Stress Modulate Hairmentioning
confidence: 99%
See 1 more Smart Citation